The TO STUDY ANTIBIOTIC SUSCEPTIBILITY PATTERN OF STAPHYLOCOCCUS AUREUS ISOLATED FROM VARIOUS SKIN SAMPLES - NEHA; BHARTI MITTU; ZARINA BEGUM; HARJOT PAL KAUR (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The study was carried out to check the antibiotic susceptibility profile of Staphylococcus aureus. Methods: In this study for the isolation of strain, skin swabs from different parts of the body were taken aseptically with the set protocol. The sensitivity patterns of S. aureus were explored with different antibiotics for the treatment of S. aureus infections. We have studied the susceptibility pattern of various antibiotics including present all line therapies and other antibiotics using disk-diffusion method. Results: It has been found that bacteria show the highest sensitivity toward third-line antibiotic tetracycline, trimethoprim, and minocycline. The different concentrations of these antibiotics were used to check the minimum inhibitory concentration and found to be effective even at the lower concentration of 0.01 mcg/disc. Furthermore, the minimum inhibitory concentration of each antibiotic has been calculated to find the most effective antibiotic at low concentration. The isolates are found to be highly resistant toward ampicillin, ciprofloxacin, and cefotaxime. Conclusion: The research concluded that the bacteria S. aureus are found to be more sensitive for chloramphenicol, kanamycin, and trimethoprim in first-line antibiotics, second-line antibiotics, and third-line antibiotics, respectively.